Lower extremity kinematic and kinetic asymmetries during running - Stiffler-Joachim, M. R.; Lukes, D.; Kliethermes, S. A.; Heiderscheit, B. C. (Medicine & Science in Sports & Exercise, 2021)
Between-limb asymmetries during running are often evaluated to assess injury risk or recovery. Asymmetries less than 10% are generally considered normal, but it is unknown if asymmetries vary depending on the metric of interest, the athlete`s sex, or running speed.